Evaluasi Keterampilan Matematika dengan Penilaian Autentik di SDN Pondok Pinang 05 Jakarta Selatan - Ina Magdalena; Muhammad Iqbal Bustomi; Nur Aisyah; Silmi Lisani (RC-INSTITUT, 2020)
The change of the KTSP curriculum into the 2013 curriculum lead to changes in the assessment system. With the change in the valuation system, teachers should be able to adapt and develop appropriate assessments with the curriculum has changed. In this 2013 curriculum using an authentic assessment system that can assess the competence of the three domains, namely the domain of attitudes, knowledge, and skills. The problems revealed in this study are Is authentic assessment instrument in the skill of mathematics which has been prepared by the teacher in accordance with the characteristics of the curriculum in 2013? Goals to be achieved in this study was to determine the suitability of authentic assessment instrument in the skill of mathematics that had been developed by teachers with the characteristics of curriculum assessment in 2013, this is a type of qualitative research that uses qualitative descriptive approach. The population in this study is an elementary school in Indonesia is SDN Pondok Pinang 05 who has applied in the process of learning curriculum was radically 2013.